Pengembangan Media Pembelajaran Modul Interaktif Menggunakan Lectora Inspire Pada Mata Pelajaran Simulasi Dan Komunikasi Digital - Yenni anty; Zainuddin Untu; Dydik Kurniawan (Universitas Muhammadiyah Surabaya, 2021)
Abstract: This study aims to develop and determine the feasibility of learning media for desktop-based interactive modules on digital citizenship material at SMK TI Airlangga Samarinda for the 2020/2021 academic year. The type of research used is Research and Development (R&D). The results of this study are: 1) Development of desktop-based Interactive Module learning media on Simulation and Digital Communication subjects with theapplication Lectora Inspire. 2) The feasibility test can be seen in the questionnaire results obtained from three media experts with 23 indicators, the total score is 268 out of a maximum score of 345 with the category